2022
DOI: 10.1084/jem.20212525
|View full text |Cite
|
Sign up to set email alerts
|

A CMV-induced adaptive human Vδ1+ γδ T cell clone recognizes HLA-DR

Abstract: The innate and adaptive roles of γδ T cells and their clonal γδ T cell receptors (TCRs) in immune responses are still unclear. Recent studies of γδ TCR repertoire dynamics showed massive expansion of individual Vδ1+ γδ T cell clones during viral infection. To judge whether such expansion is random or actually represents TCR-dependent adaptive immune responses, information about their cognate TCR ligands is required. Here, we used CRISPR/Cas9-mediated screening to identify HLA-DRA, RFXAP, RFX5, and CIITA as req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…3A–G ). It was recently demonstrated that γδ T cells can recognize HLA-DR in CMV-infected cells 26 , but the MCC26 cell line does not express HLA-DR, DP, or DQ (Supplementary Fig. 3H ).…”
Section: Resultsmentioning
confidence: 95%
“…3A–G ). It was recently demonstrated that γδ T cells can recognize HLA-DR in CMV-infected cells 26 , but the MCC26 cell line does not express HLA-DR, DP, or DQ (Supplementary Fig. 3H ).…”
Section: Resultsmentioning
confidence: 95%
“…Over childhood, Vδ1 and Vδ2 cells exhibit increased clonal expansions, dissemination across sites, and functional maturation to cytolytic effectors—features consistent with antigen-driven differentiation. Clonal expansion of γδ T cells has been observed in response to infections in malaria ( 78 ) and CMV ( 79 ). This functional convergence of Vδ subsets and progression to a terminally differentiated state is accompanied by a loss of tissue γδ T cells in frequency (and density) ( 46 ) in mucosal sites in adults.…”
Section: Discussionmentioning
confidence: 99%
“…The early expansion and increase in HLA-DR expression of Vδ1 T cells could be the result of a general increase in activated immune cells, although HLA-DR increase was first noted in Vδ1 T cells among T cell subsets. Notably, CMV-induced adaptive Vδ1 T cells have been recently shown to recognize HLA-DR on activated immune cells, pointing to their role in inflammation-induced MHC-dependent immune response 48 .…”
Section: Discussionmentioning
confidence: 99%